2013
DOI: 10.1586/ers.12.85
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and corticosteroids in asthma: synergy, interaction and potential therapeutic effects

Abstract: The mechanisms reviewed … in addition to the results of the clinical studies, strengthen the notion of a synergy between corticosteroids and vitamin D, which may have particular relevance for asthma and allergies. Larger studies in humans will be needed to verify this synergy, and to determine its clinical use."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…A large number of observational studies subsequently linked vitamin D deficiency with a broad range of undesirable metabolic, immune and clinical outcomes (6,7). These include the risk of developing and/or surviving cancer (8)(9)(10), influenza epidemics (11), other respiratory infections (12)(13)(14), asthma (15)(16)(17)(18)(19), food allergies (20), inflammatory bowel diseases (21), obesity (22) and several chronic inflammatory disorders (6,23). One consequence of such research has been that a high level of self-medication with exogenous vitamin D now occurs in many countries, much as extensive high-level vitamin C supplementation became popular for its presumed benefits on the common cold and cancer survival between 1970 and the late 1980s.…”
mentioning
confidence: 99%
“…A large number of observational studies subsequently linked vitamin D deficiency with a broad range of undesirable metabolic, immune and clinical outcomes (6,7). These include the risk of developing and/or surviving cancer (8)(9)(10), influenza epidemics (11), other respiratory infections (12)(13)(14), asthma (15)(16)(17)(18)(19), food allergies (20), inflammatory bowel diseases (21), obesity (22) and several chronic inflammatory disorders (6,23). One consequence of such research has been that a high level of self-medication with exogenous vitamin D now occurs in many countries, much as extensive high-level vitamin C supplementation became popular for its presumed benefits on the common cold and cancer survival between 1970 and the late 1980s.…”
mentioning
confidence: 99%
“…Vitamin D enhances steroid‐induced interleukin‐10 secretion and MAPK phosphatase 1 expression to produce increased anti‐inflammatory effects. Vitamin D also suppresses inflammation by enhancing both corticosteroid inhibition of proinflammatory chemokines such as RANTES (regulated upon activation normal T‐cell expressed and secreted) and corticosteroid induction of a tolerogenic dendritic cell phenotype 16 . But the current study by Zator et al is the first to specifically show the link between vitamin D status and anti‐TNFα therapy.…”
mentioning
confidence: 69%
“…Lastly, Litonjua,112 in his review, examined whether the administration of vitamin D enhances corticosteroid actions and potentially reverses steroid resistance, a crucial topic for asthmatic patients. As it has already been mentioned in the present review, several clinical and observational studies have suggested a synergistic effect of vitamin D and corticosteroids in asthma outcomes 83,92,93,96.…”
Section: Resultsmentioning
confidence: 99%